2020
DOI: 10.1016/j.molp.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Nucleotides Substitution in Plant Using an Improved Prime Editing System

Abstract: In addition, for BEs, the target bases are limited to an editing window of at least three nucleotides (nt) away from the 5 0 end of the protospacer adjacent motif (PAM), and undesired base substitutions are common, especially when several Cs or As coexist in the editing window (Chen et al., 2019). Although CRISPR/Cas-mediated homologous recombination provides an alternative method for precise targeted gene replacement or gene insertion in plants, it is limited by the low efficiency (Miki et al., 2018). Most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 10 publications
1
88
0
Order By: Relevance
“…Very recently, several reports have shown that prime editing can be applied to cereal plants Lin et al, 2020;Tang et al, 2020;Xu et al, 2020a;Xu et al, 2020b;Butt et al;Hua et al). All these studies showed that the efficiency of PPEs greatly varies between target sites and is sensitive to several parameters such as both the PBS and RT sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, several reports have shown that prime editing can be applied to cereal plants Lin et al, 2020;Tang et al, 2020;Xu et al, 2020a;Xu et al, 2020b;Butt et al;Hua et al). All these studies showed that the efficiency of PPEs greatly varies between target sites and is sensitive to several parameters such as both the PBS and RT sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The highest editing efficiencies achieved by the five groups ranged from 2.22% to 31.3% [2,3,5,6,8]. Of the total 164 primeedited rice lines, only one line, generated by Xu et al [6], harbors homozygous mutations; all the other lines mainly harbor chimeric mutations. These results indicate that the reported primeediting tools require significant optimization before they are adopted for use by plant researchers.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, a novel and universal precision genome-editing technology named prime editing was developed and tested in mammalian cells [1]. More recently, seven groups reported applications of prime editors (PE) in rice and wheat, and six groups achieved prime-edited rice lines [2][3][4][5][6][7][8]. Excluding the data based on enriching strategies or that are unsuitable for comparison, a total of 164 prime-edited rice lines transformed with 39 prime editors targeting 11 endogenous rice genes were generated in these previous reports [2,3,5,6,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations